Metodología de enseñanza universitaria y aplicación de criterios innovadores en la docencia de Ciencias Administrativas y Contables de la Universidad Peruana los Andes - Sánchez Soto, Juan Manuel (2020)
The objective of this study was to establish the relationship between the methodology of university education and the application of innovative teaching criteria that are given in the Faculty of Administrative and Accounting Sciences of the Peruvian University Los Andes. For this, a quantitative research and correlational-descriptive design was proposed. The research method used was the hypothetical-deductive. The study population consisted of the students of the Faculty: a total of 3795 students enrolled in the 2019-I academic year. Using a finite probabilistic sampling, the sample was determined, consisting of 150 students. The results show that there is a significant relationship between the university teaching methodology variable and the teaching innovation criteria variable (rs = 0.732, p <0.05) at a medium positive level.   DOI: https://doi.org/10.31876/sl.v4i1.47